ASSOCIATION BETWEEN NUTRITION AND ORAL HEALTH OF SCHOOL HEALTH PROGRAM PARTICIPANTS IN THE MUNICIPALITY OF SCHOOL MOSSORÓ / RN (Fiep Bulletin - online, 2015)
The objective of this study was to analyze the association between nutritional status and oral health of school children at the School Health Program of the municipality of Mossoró. The samples were collected at four public schools, the sample comprised 403 pupils aged between 7 and 15 years entered into the Health Program enrolled in primary school, four schools represent each health region town of Mossoró/RN where they achieved good development indices in the program,. For quantitative data analysis of oral health and nutritional status of schoolchildren descriptive statistics One Way ANOVA was used. For the association use the index of the coefficient of Pearson correlation in the independent variables (p?0,05). Analysis of nutritional status revealed that students in the program mostly are the perfect weight for your height, in relation to oral health the highest average found in a particular region in DMFT clinical examination was 4.3, no statistically strong relationship of this variable with the body mass index of the participating school. It is therefore concluded that there was no statistically significant relationship between nutritional status and oral health of schoolchildren.
Keywords: Health; School; Multidisciplinary.